Teoria Formy Otwartej i Linearny System Ciągły. O poszukiwaniach założeń koncepcji Oskara Hansena w obecnej rzeczywistości przestrzennej Poznania - Sulikowska, Aleksandra (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2017)
This article is devoted to the theoretical legacy of Oskar Hansen - Theory of Open Form and Linear Continuous System. Oskar Hansen was a Polish architect who began his activities during the Modernism. The impulse to write this article was given by the publication of Zaczyn. O Zofii i Oskarze Hansenach by Filip Springer. The author of that book has recalled Hansen’s architectural achievements. The article oscillates around the figure of Oskar Hansen, his concepts and accomplishments. From the point of this publication it was important to define the objectives of the concepts of the Theory of Open Form and Linear Continuous System. The purpose of the article was to point out architectural fulfilment of Hansen’s theoretical assumptions in already existing contemporary Poznań’s spatial reality and present new ones that are planned.